Triblock-Diblock Composite Nanoassemblies with Sequentially Addressable Host-Guest Properties for Hydrophobics and Hydrophilics - Zhuang, Jiaming (ACS Macro Lett, 2020)
Noncovalent encapsulation of multiple guest molecules with distinct physiochemical properties, especially hydrophilic and hydrophobic guests, into a single polymeric nanoassembly is challenging, but would be profoundly beneficial to combination therapeutic delivery strategies. Here, we report a nanocomposite co-assembled by coating a layer of an amphiphilic block copolymer onto surface of a crosslinked inverse micelle driven by hydrophobic interactions. The hydrophobic coating layer and water-filled inverse micelles were utilized to encapsulate hydrophobic and hydrophilic cargos respectively. Rationally introducing the pH and redox responsive moieties into coating polymer and inverse micelles, allows sequentially addressing triggered release of the encapsulated cargos.